Baseline quality of life in people with hip fracture: results from the multicentre WHiTE cohort study - Parsons, N; Costa, ML; Achten, J; Griffin, X (British Editorial Society of Bone and Joint Surgery, 2020)
Aims To assess the variation in pre-fracture quality of life (QoL) within the UK hip fracture population, and quantify the nature and strength of associations between QoL and other routinely collected patient characteristics and treatment choices.